PERSPEKTIF KEPEMIMPINAN MISIO DEI NEHEMIAH BAGI KEMAJEMUKAN INDONESIA DALAM MEMBANGUN IMAN DAN KESEJAHTERAAN BANGSA - Masola, Pabian Lelang (STT Kingdom, 2024)
Leadership is a person's ability to influence other people, to carry out the same actions, as well as someone who dares to take risks and can be responsible for their actions. The actions of a respected leader do not depend solely on the abilities above, he is respected only if he acts fairly and without considering the ethnicity, social status and religion of the people he leads. Without justice, leaders will act anarchically and arbitrarily towards the people who are led specifically by the common people. In relation to government, the leader must be someone appointed by God, because he carries out God's duties in this world. So the leader chosen by Allah should be someone who fears Allah. Because if a leader does not fear God he will act outside of God's truth. People who fear God can be seen in several aspects of life, namely; morals based on God's truth, living in association with God (worship), honest, not compromising with sin, carrying out God's commands, prioritizing the welfare of the people rather than the group. This research is based on qualitative descriptive methods. Observations of the condition of the Indonesian people show that the people need leaders who are just and fear God. Indonesia has been divided with various political content and even has a status labeled Religion. Indonesia is on the verge of destruction if the leaders are people who do not fear God, besides that they also do not uphold the constitution of the Republic of Indonesia.